Acceptance and commitment therapy for young brain tumour survivors: study protocol for an acceptability and feasibility trial. Issue 6 (1st June 2021) - Malins, Sam; Owen, Ray; Wright, Ingram; Borrill, Heather; Limond, Jenny; Gibson, Faith; Grundy, Richard G; Bailey, Simon; Clifford, Steven C; Lowis, Stephen; Lemon, James; Hayes, Louise; et al.
Abstract : Introduction: Survivors of childhood brain tumours have the poorest health-related quality of life of all cancer survivors due to the multiple physical and psychological sequelae of brain tumours and their treatment. Remotely delivered acceptance and commitment therapy (ACT) may be a suitable and accessible psychological intervention to support young people who have survived brain tumours. This study aims to assess the feasibility and acceptability of remotely delivered ACT to improve quality of life among these young survivors. Methods and analysis: This study is a two-arm, parallel group, randomised controlled trial comparing ACT with waitlist control at 12-week follow-up as the primary endpoint. Seventy-two participants will be recruited, who are aged 11–24 and have completed brain tumour treatment. Participants will be randomised to receive 12 weeks of ACT either immediately or after a 12-week wait. The DNA-v model of ACT will be employed, which is a developmentally appropriate model for young people. Feasibility will be assessed using the proportion of those showing interest who consent to the trial and complete the intervention. Acceptability will be assessed using participant evaluations of the intervention, alongside qualitative interviews and treatment diaries analysed thematically. A range of clinical outcome measures will also assess physical and mental health, everyday functioning, quality of life and service usage at 12-week follow-up. The durability of treatment effects will be assessed by further follow-up assessments at 24 weeks, 36 weeks and 48 weeks. Ethics and dissemination: Ethical approval was given by East Midlands, Nottingham 1 Research Ethics Committee (Reference: 20/EM/0237). Study results will be disseminated in peer-reviewed journals, through public events and relevant third sector organisations. Trial registration: ISRCTN10903290 ; NCT04722237 .